Visual design of dialogue flows for conversational interfaces. Issue 10 (27th July 2021) - Valtolina, Stefano; Neri, Lorenzo
ABSTRACT: Nowadays, new technologies are taking place for enabling conversational interactions between users and bots. Creating conversational interfaces (CI) paves the way for new design challenges. Designers need to use appropriate design specifications for creating a logically sound dialogue endowed with proper visual cues in the case of chatbots that captures the entire user experience. To do it they need the help of domain experts. Experts in mobility, environment, energy, e-health, weather, etc., are the only ones who well-know the specific domain in which the bot will act. Current tools used to design interactive flows of dialogue entail deep programming skills their users need to know. Starting from this consideration, the paper proposes a design environment that offers experts the possibility to design a flow of dialogue without getting lost in technicalities. By using visual language, the expert can specify intents, actions, entities and parameters at the base of the flow of dialogue on which the bot will be created. Then, our engine automatically translates into a bot compliant with the Google DialogFlow technology. Finally, the paper present a preliminary analysis of the system carried out to test its features and how these are reflected in its ease of use.